The value of bali's local wisdom on hotel employees in badung regency - Astina, Made Arya (Journal of Business on Hospitality and Tourism, 2021)
The island of Bali is famous as one of the most popular tourist destinations in the world. Thus, the development of Bali tourism from year to year is strongly influenced by various factors. Culture becomes an important factor for tourists choosing Bali as their preferred tourist destination. In order to support the tourism, the human resource also becoming the significant aspect that need to be taken into account. Given the importance of the role of human resources in the tourism sector, especially in the hospitality subsector, this study analyzed the value of Bali's local wisdom among star hotels in Badung regency. this study also wanted to find out how the phenomenon of local wisdom value in Bali, especially in Badung regency. Identification of the value of local Balinese wisdom is expected to gain contribution of ideas and thought in human resource development to the hospitality sub-sector in Bali in general, and Badung Regency in particular. Through literature studies and questionnaire consisted of  34 questions to measure the six cultural dimension such as Power Distance, Individualism vs. Collectivity, Masculinity vs. Femininity, Uncertainty Avoidance, Long-term orientation vs. Short-term orientation, and Indulgence vs. Restraint, the data then analysed through the VSM (value survey module) developed. The results shows that Badung regency’s star hotels’ employees have a culture with a high level of collectivism, shows a low power distance value, tend to have Feminine culture, have a culture with a relatively low level of Uncertainty Avoidance